Effect of drought stress on gas exchange characteristics of four soybean genotypes (Bangladesh Journal of Agricultural Research, 2016)
An experiment was conducted in a venylhouse at the environmental stress site of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during September to December 2012 to determine the changes of photosynthesis and some related traits under drought stress in soybean genotypes. Four studied genotypes viz. Shohag, BARI Soybean 6 and BD2331 (relatively stress tolerant) and BGM2026 (susceptible) were tested against two water regimes such as water stress and non-stress. Results indicated that gas exchange characteristics were positively correlated with plant growth. Photosynthesis and stomatal conductance showed more reduction in susceptible genotypes than the tolerant ones. Transpiration rate was found minimal in tolerant genotypes. Changes in leaf growth attributes of the four selected genotypes were compared under drought (water) stress conditions which is one of the major plant parts related to gas exchange. Generally, drought stress decreased the leaf area more in susceptible genotype than tolerant genotype. From the result, genotype BGM2026 which recorded the lowest photosynthesis, stomatal conductance, leaf area but highest transpiration rate was considered as drought susceptible whereas BARI Soybean-6, Shohag and BD2331 were more drought stress tolerant which have better mechanisms of drought tolerance.Bangladesh J. Agril. Res. 41(2): 195-205, June 2016